The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011 IEEE International Conference on Computer Vision Workshops (ICCV Workshops) 2011
DOI: 10.1109/iccvw.2011.6130321
|View full text |Cite
|
Sign up to set email alerts
|

Real-time visual odometry from dense RGB-D images

Abstract: We present an energy-based approach to visual odometry from RGB-D images of a Microsoft Kinect camera. To this end we propose an energy function which aims at finding the best rigid body motion to map one RGB-D image into another one, assuming a static scene filmed by a moving camera. We then propose a linearization of the energy function which leads to a 6 × 6 normal equation for the twist coordinates representing the rigid body motion. To allow for larger motions, we solve this equation in a coarse-to-fine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
252
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(255 citation statements)
references
References 8 publications
(7 reference statements)
0
252
1
2
Order By: Relevance
“…The sequences are labeled with 6-DOF ground truth from a motion capture system having 10 cameras. Six research publications about evaluating ego-motion estimation and SLAM over TUM Benchmark dataset are [21,38,45,84,86,87].…”
Section: Tum Benchmark Datasetmentioning
confidence: 99%
“…The sequences are labeled with 6-DOF ground truth from a motion capture system having 10 cameras. Six research publications about evaluating ego-motion estimation and SLAM over TUM Benchmark dataset are [21,38,45,84,86,87].…”
Section: Tum Benchmark Datasetmentioning
confidence: 99%
“…However, they are not able to properly cope with large displacements between consecutive frames. In [13], it has been experimentally shown that the performance of the method degrades as the frame interval increases, which is equivalent to decreasing the frame rate of the acquisition, or increasing the sensor velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, odometry methods that take advantage of the depth and color information provided by RGB-D sensors have been developed [9,13]. They run in real-time and provide accurate estimations for high frame rate acquisitions and moderate sensor velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate 3D reconstruction and mapping has been addressed as a vital topic and is playing a prominent role in such important research domains as 3D shape acquisition and modelling, surface generation and texturing, localization and robot vision (Engelhard et al, 2011;Newcombe et al, 2011a;Steinbrucker et al, 2011;Whelan et al, 2012a;Whelan et al, 2013). During recent years, the advent of powerful generalpurpose GPUs has resulted in the first generation of real-time 3D-reconstruction applications which use depth data obtained from a low-cost depth Kinect sensor (PrimeSense; Kinect; Asus) to generate 3D geometry for relatively large and complex indoor environments (Newcombe et al, 2011b;Izadi et al, 2011;Bondarev et al, 2013;Whelan et al, 2012b;Whelan et al, 2012a;Whelan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%